Comparison of different induction techniques on hemodynamic changes in pediatric patients undergoing infra umbilical surgeries using laryngeal mask airway - Amrina Ashraf,; Shafat A Mir,; Khalid Sofi,; Majid Jehangir,; Akbar Shah M,; Altaf Hussain Mir, (Asian Journal of Medical Sciences, 2024)
Background: Post-induction hypotension associated with various agents is well-known in adults undergoing general anesthesia for various procedures. However, this phenomenon has not been addressed well in pediatric patients. We studied the incidence of postinduction hypotension in patients 1–5 years using inhalational induction with sevoflurane, intravenous induction with propofol, and co-induction with sevoflurane plus propofol. Aims and Objectives: To compare three different induction techniques in children 1–5 years undergoing various infra-umbilical surgeries under general anesthesia with laryngeal mask airway using sevoflurane induction, propofol induction, and sevoflurane plus propofol co-induction. Materials and Methods: Out of 150 patients observed in this study, 50 patients (group S) received inhalational induction with sevoflurane, 50 (group P) patients received intravenous induction with propofol, and 50 (group SP) patients received co-induction with propofol and sevoflurane. Results: Intravenous induction with propofol resulted in maximum hemodynamic changes Inhalational induction was responsible for significant changes in heart rate whereas co-induction with propofol (1–1.5 mg/kg) and sevoflurane 5% yielded minimum hemodynamic variations with least adverse effects. Conclusion: We conclude that co-induction with propofol (1–1.5 mg/kg) plus Sevoflurane 5% provided better hemodynamic stability with the least adverse effects.